Gambaran Perilaku Hidup Bersih Dan Sehat (PHBS) Santriwati Pesantren X Pada Masa Pandemi Covid-19 Di Kabupaten Bogor Tahun 2022 - Komariah, Nur Lathifa; Iriani, Dewi U (Journal of Religion and Public Health, 2024)
During the Covid-19 pandemic, everyone is required to behave healthily. One of the efforts is Clean and Healthy Living Behavior (PHBS). Pesantren is a traditional Islamic educational institution where students live together and study under the guidance of teachers. Based on research, the lack of PHBS practices among students causes many students to suffer from infectious diseases such as scabies, ISPA, gastritis, and helminthiasis. This study aims to determine the description of the PHBS of female students during the pandemic at Pesantren X, Bogor Regency in 2022. This research was a cross-sectional study design with 278 female students as samples taken by random sampling method. PHBS habits during the pandemic were carried out by female students such as washing hands with soap (CTPS), using masks, maintaining distance, disposing of waste, using latrines, brushing teeth, taking deworming drugs, and physical activity were asked through interviews. Variable analysis used frequency distribution. The results showed that most of the female students had good CTPS (50 %), mask use (51.4%), physical distancing (52.2%), waste disposal behavior (60.8 %), menstrual health management (60.8%), latrine use (66.5%), tooth brushing (53.2%), deworming behaviour (53.2%) and physical activity (59%). However, CTPS behavior had the smallest percentage at 50%. This CTPS behavior is high risk in the spread of Covid-19 and other infectious diseases. Thus, it is necessary to re-educate female students regarding the importance of CTPS and the issuance of policies from Pondok Pesantren administrators related to monitoring CTPS behavior.Keywords: Pandemic, Pesantren, PHBS